Mitigating greenhouse gas emissions from irrigated rice cultivation through improved fertilizer and water management - Mofijul Islam, Shofiqul M.; Gaihre, Yam Kanta; Islam, Rafiqul; Ahmed, Nayeem; Akter, Mahmuda; Singh, Upendra; Sander, Björn Ole (Elsevier, 2022)
Greenhouse gas (GHG) emissions from agriculture sector play an important role for global warming and climate change. Thus, it is necessary to find out GHG emissions mitigation strategies from rice cultivation. The efficient management of nitrogen fertilizer using urea deep placement (UDP) and the use of the water-saving alternate wetting and drying (AWD) irrigation could mitigate greenhouse gas (GHG) emissions and reduce environmental pollution. However, there is a dearth of studies on the impacts of UDP and the integrated plant nutrient system (IPNS) which combines poultry manure and prilled urea (PU) with different irrigation regimes on GHG emissions, nitrogen use efficiency (NUE) and rice yields. We conducted field experiments during the dry seasons of 2018, 2019, and 2020 to compare the effects of four fertilizer treatments including control (no N), PU, UDP, and IPNS in combination with two irrigation systems— (AWD and continuous flooding, CF) on GHG emissions, NUE and rice yield. Fertilizer treatments had significant (p < 0.05) interaction effects with irrigation regimes on methane (CH4) and nitrous oxide (N2O) emissions. PU reduced CH4 and N2O emissions by 6% and 20% compared to IPNS treatment, respectively under AWD irrigation, but produced similar emissions under CF irrigation. Similarly, UDP reduced cumulative CH4 emissions by 9% and 15% under AWD irrigation, and 9% and 11% under CF condition compared to PU and IPNS treatments, respectively. Across the year and fertilizer treatments, AWD irrigation significantly (p < 0.05) reduced cumulative CH4 emissions and GHG intensity by 28%, and 26%, respectively without significant yield loss compared to CF condition. Although AWD irrigation increased cumulative N2O emissions by 73%, it reduced the total global warming potential by 27% compared to CF irrigation. The CH4 emission factor for AWD was lower (1.67 kg ha− 1 day− 1) compared to CF (2.33 kg ha− 1 day− 1). Across the irrigation regimes, UDP increased rice yield by 21% and N recovery efficiency by 58% compared to PU. These results suggest that both UDP and AWD irrigation might be considered as a carbon-friendly technology.